BENTUK, FUNGSI DAN MAKN A REGISTER KOMUNITAS PECINTA AQUASCAPE DI ROKAN HULU - Nuratika Nuratika; Hasnul Fikri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
The diversity of language use in a heterogeneous society gives rise to language variations, including registers. The Aquascape Lovers Community in Rokan Hulu uses a separate register. This study aims to describe the form, function, and meaning of the limited and open circle register in the Aquascape Lovers Community in Rokan Hulu. This research is quantitative research with a descriptive method. Listening and recording methods were used in data collection. The informant is a Community of Aquascape Lovers in Rokan Hulu. The data were analyzed qualitatively by referring to the concept of form, function, and meaning of closed registers and closed registers proposed by Halliday. The results of the study are as follows. First, the limited circle register of the Aquascape Lovers Community in Rokan Hulu at the level of words and phrases in the form of abbreviations and the use of foreign words such as WC, kebo, and sticky rice with interactional and personal functions. Each word and phrase has a specific meaning. Second, the open circle register of the aquascape lover community in Rokan Hulu at the word and phrase-level in the form of abbreviations and the use of foreign words such as PH, lily pipe, and surface scum with interactional, heuristic, and regulatory functions. Each word and phrase has a specific meaning. It can be concluded that some of the registers used by this community can only be understood by community members and some can also be understood by people outside the community.